MANAJEMEN PERSIAPAN KELAHIRAN HINGGA PROSES PENYAPIHAN BELO PASCA LAHIR - , EPRY SETIAWAN, drh. Erif Maha Nugraha setyawan., M.Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Natal preparation management until belo pasca's weaning process comes into the world at ranch rides on horseback Tombo Ati Stable covers natal preparation, time handle comes into the world, pasca's handle bears, care before weaning, den managery, weft managery, exercise. Action that is done is follow all full parented care activity and belo face to face with den officer. Care management rides on horseback at Tombo Ati Stable in particular natal preparation management until belo pasca's weaning process comes into the world was performed with every consideration and appropriate standard one a lot of used by stable who is at Indonesia. Tombo Ati Stable realises that full parented care and belo has momentous role in maximize success in continent horse. Opus writes this constitute result of field work practice that is done at about breed Tombo Ati Stable belongs to Ir. H. Munawir's Muhammad that gets location at orchard Needs, Tengaran's district, Salatiga's municipality, about natal preparation management until belo's weaning process. Acquired data is taken straightforward which is observations straightforward writer at the site with Tombo Ati Stable's den officer, writer does interview with Tombo Ati Stable's den officer, borrowing book recording about proprietary horse health by Tombo Ati Stable. Result of natal preparation management watch until weaning process that is done at Tombo Ati Stable in a general way was good.